Paul's Charismatic Imperatives - Kagarise, Robby (Journal of Pentecostal Theology Supplement Series, 2014)
Do not quench the Spirit! Strive for spiritual gifts! Walk in the Spirit! In these imperatives, all from the hand of Paul, the apostle regards the success of the Spirit's work as dependent on human cooperation. Does Paul's linking of divine power with human agency derive from the influences of his religious background, or is it a product of his own experience and thought? How does Paul think of the interrelation between Spirit and human agency? As the author answers these questions we are given an illuminating view both of the path along which Paul thinks the Spirit draws believers, and of the nature of the Spirit's activity that Paul expects believers to embrace. This book will be welcomed by scholars and students working in the field of Pauline pneumatology and both scholarly and lay readers interested in the implications of Pauline pneumatology for Pentecostal/Renewal theology and practice.